Phakomatosis Pigmentovascularis Coexisting with a Variant of Sturge Weber Syndrome - A Rare Occurrence - Priyanka Singh; Nayana A. Potdar; Ankita Patil; Pritam K. Mohite; Chhaya A. Shinde; Pooja Bandivadekar (Delhi Journal of Ophthalmology)
The spectrum of phacomatoses is wide and they share common pathophysiological changes. The various entities widely studied and being reported are Sturge Weber Syndrome (SWS), Klippel Trenaunay Syndrome and Phakomatosis Pigmentovascularis (PPV). Here we report a rare case of coexisting Phakomatosis cesioflaemmea type of PPV along with a type 1 variant of Sturge Weber Syndrome. Co-existence of PPV with SWS is known but rare. Management of ocular manifestation especially glaucoma, is challenging in such neurocutaneous conditions but this particular case responded well to medical therapy for glaucoma. This case will help us broaden our outlook when dealing with various phakomatosis, keeping in mind overlapping signs of different syndromes and tendency of few syndromes to increase preponderance to malignant transformation which will require close follow up for the same.